From Transformational Leadership to Social Entrepreneurship: Strengthening Innovation and Sustainability in Faith-Based Organizations - Muhammad Hafidh Nasrullah; Sukesi Sukesi; Slamet Riyadi (Al-Qalam Institute, 2026)
This study aims to analyze the influence of transformational leadership, social entrepreneurship, and social capital on pesantren performance in East Java through creativity and social value creation. This study employed an explanatory quantitative approach with a causal-predictive design. Data were collected from pesantren leaders and business unit managers and analyzed using SEM-PLS with SmartPLS 4.1. The results show that all constructs met the validity and reliability criteria. Transformational leadership, social entrepreneurship, and social capital positively affect creativity, while transformational leadership and social entrepreneurship influence social value creation. The research model explains 61.2% of the variance in pesantren performance. The discussion confirms that creativity serves as the main mechanism that transforms leadership capacity, entrepreneurial orientation, and relational resources into improved institutional performance. In conclusion, pesantren performance is more effectively strengthened through creativity-based organizational innovation than through social value creation, which has not yet been fully measured. The implication is that pesantren need to strengthen governance, social performance indicators, and entrepreneurial management systems. These findings extend the literature on leadership and social entrepreneurship in faith-based organizations and provide empirical relevance for pesantren institutional development.